The role of the hippocampus and retrosplenial cortex in spatial memory: a double blind anodal transcranial direct current stimulation study - De Biase, Rosalia; Esposito, Sara; Chiaramello, Emma; Parazzini, Marta; Sagliano, Laura (Frontiers in Human Neuroscience, 2025)
IntroductionSpatial memory supports orientation and navigation by integrating multiple spatial reference frames. Neuroimaging and lesion studies implicate the hippocampus (HIP) and retrosplenial cortex (RSC), but causal evidence from non-invasive brain stimulation is limited.MethodsEighteen participants performed a spatial localization task in a virtual room under three stimulation conditions: anodal transcranial direct current stimulation (tDCS) over the left RSC, anodal tDCS over the left HIP, and sham. Task conditions varied in reference frame (viewer-, object-, room-centered) and perspective shift (0°, 45°, 135°). Accuracy was analyzed with non-parametric statistics.ResultsPerformance declined with increasing viewpoint rotation, especially in room-centered trials. RSC stimulation selectively reduced accuracy in room-centered trials with large perspective shifts (135°), whereas HIP stimulation did not significantly modulate performance.DiscussionFindings provide causal evidence for the involvement of the RSC in viewpoint-invariant spatial updating, supporting its role in integrating stable environmental cues. HIP stimulation yielded no reliable behavioral effects, suggesting functional specificity of the RSC and highlighting the challenges of modulating deep cortical structures with tDCS.